2020
DOI: 10.1080/02770903.2020.1827424
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric asthma hospitalization: individual and environmental characteristics of high utilizers in South Texas

Abstract: Objective: Few studies have examined factors affecting the high frequency of hospitalization for pediatric asthma. This study identifies individual and environmental characteristics of children with asthma from a low-income community with a high number of hospitalizations. Methods: The study population included 902 children admitted at least once to a children's hospital in South Texas because of asthma from 2010 to 2016. The population was divided into three groups by utilization frequency (high: !4 times, me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(28 citation statements)
references
References 45 publications
0
28
0
Order By: Relevance
“…There were six studies [ 9 , 10 , 11 , 12 , 13 , 22 ] using the odds ratio (OR) to assess the likelihood of readmission rate due to outdoor exposure. Findings for these can be found in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…There were six studies [ 9 , 10 , 11 , 12 , 13 , 22 ] using the odds ratio (OR) to assess the likelihood of readmission rate due to outdoor exposure. Findings for these can be found in Table 2 .…”
Section: Resultsmentioning
confidence: 99%
“…The air pollutant models were also adjusted for temperature. As Baek et al (2020) [ 13 ] was a substudy of Baek et al (2020) [ 12 ], the exposure is essentially the same; however, the air pollutants were both measured using the daily average prediction from the reliable United States of America environmental protection agency (U.S. EPA) Downscaler model [ 25 ], which were then divided into four categories (quartile 1 (the lowest) to quartile 4 (the highest)). In contrast, Beck et al (2017) [ 17 ] utilised the Health and Environmental Opportunity Index (HEOI) [ 26 ] as the exposure variable.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Pulmonary function tests were used to evaluate the prevalence of asthma in children in areas with high and low ozone concentrations, and it was found that ozone pollution would increase the prevalence of asthma ( 12 ). Moreover, high levels of ozone may increase the number of hospitalizations in children with asthma ( 13 ). A study from South Texas that included 902 children who were hospitalized for asthma at least twice found that a higher level of ozone was significantly associated with an increased number of children hospitalized for asthma.…”
Section: Discussionmentioning
confidence: 99%